EFEITOS DO TREINAMENTO FÍSICO AERÓBICO SOBRE A FUNÇÃO VASCULAR DE RATOS COM SOBRECARGA CRÔNICA DE FERRO - Rossi, Emilly Martinelli (2020)
Physical exercise is an effective non-pharmacological approach for prevention and treatment of cardiovascular diseases. Also, because iron is essential element in many physiological processes including hemoglobin and myoglobin synthesis, thereby playing a